Optimization Of Production Employee Shift Scheduling Using The Simple Additive Weighting Method At PT Japfa Comfeed Gedangan: Optimasi Penjadwalan Shift Karyawan Produksi Dengan Metode Simple Additive Weighting Di Pt Japfa Comfeed Gedangan - Rahandi Ramadhan; Rr. Rochmoeljati (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
This technical implementation study discusses the optimization of production employee shift scheduling at PT Japfa Comfeed Indonesia Tbk using the Simple Additive Weighting (SAW) and Integer Linear Programming (ILP) methods. The scheduling model applied considers performance factors, job satisfaction, work discipline, and work knowledge to form teams with balanced total values, thereby increasing work effectiveness and efficiency. The rule-based scheduling method shows more regular and consistent shift distribution results, with a "1 team 1 shift in 1 week" pattern that supports stable routines and facilitates employee adaptation. The web-based scheduling system was developed using HTML, CSS on the front-end, and PHP and MySQL on the back-end, which is equipped with security features such as authentication and authorization. The applied results successfully showed increased productivity and reduced miscommunication between teams. The use of Excel Solver and Lingo 20.0 helped optimize work schedules with more precise calculations. The applied results also made a significant contribution to human resource management, but the imbalance in workload between teams still needs to be improved. Further studies are recommended to explore machine learning-based methods, integrate the system with HRMS tools, and study the psychological and economic impacts of implementing this system.